1997
DOI: 10.1152/jappl.1997.83.3.681
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of allergic airway responses in P-selectin-deficient mice

Abstract: P-selectin is an adhesion receptor that has been shown to be important in the recruitment of eosinophils and lymphocytes in a variety of inflammatory conditions. Because cellular recruitment is thought to be a critical event in allergen-induced changes in airway responsiveness, we reasoned that P-selectin-deficient mice would exhibit reduced airway responsiveness and cellular trafficking noted in wild-type (+/+) mice. Both (+/+) and P-selectin-deficient (-/-) mice sensitized and challenged with ovalbumin (OVA/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 35 publications
(24 reference statements)
5
43
0
Order By: Relevance
“…The presence of similar levels of IL-4 in both P-selectin ϩ/ϩ and Ϫ/Ϫ mice at 7 and 10 days of allergen exposure when MCM was reduced in Ϫ/Ϫ mice further confirms previous reports that IL-4 or IL-5 is not crucial for the development of MCM (29). P-selectin Ϫ/Ϫ mice exhibited significantly lower numbers of eosinophils and lymphocytes in BALF after sensitization and challenge with OVA compared with ϩ/ϩ mice (16). The earlier decrease of MCM correlates with the earlier increase of IFN-␥ levels in Pselectin Ϫ/Ϫ mice and supports our previous finding that IFN-␥ decreases MCM by inducing programmed cell death in epithelial mucus cells (4).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The presence of similar levels of IL-4 in both P-selectin ϩ/ϩ and Ϫ/Ϫ mice at 7 and 10 days of allergen exposure when MCM was reduced in Ϫ/Ϫ mice further confirms previous reports that IL-4 or IL-5 is not crucial for the development of MCM (29). P-selectin Ϫ/Ϫ mice exhibited significantly lower numbers of eosinophils and lymphocytes in BALF after sensitization and challenge with OVA compared with ϩ/ϩ mice (16). The earlier decrease of MCM correlates with the earlier increase of IFN-␥ levels in Pselectin Ϫ/Ϫ mice and supports our previous finding that IFN-␥ decreases MCM by inducing programmed cell death in epithelial mucus cells (4).…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that allergic airway responses are reduced in sensitized and allergen-challenged P-selectin-deficient (Ϫ/Ϫ) mice (16). The purpose of the current study was to investigate whether reduced inflammation affects the development and resolution of MCM during prolonged exposure of mice to allergen and whether regulators of apoptosis may play a role in the resolution process.…”
mentioning
confidence: 97%
“…Airway responsiveness was measured as described previously (21,28,29). Methacholine dose-response curves were obtained by intravenous administration of sequentially increasing doses of methacholine (33 to 1,000 µg/kg) in a 20-to 35-µl volume.…”
Section: Methodsmentioning
confidence: 99%
“…Examination of murine models of human allergic asthma has provided novel insight into the pathobiologic events linking airway inflammation with airway dysfunction (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). In these models, systemic sensitization to ovalbumin (OVA) followed by repeated exposure to aerosolized OVA results in increased IgE production, pulmonary inflammatory cell infiltrates, and airway hyperresponsiveness (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation